Respiratory medicine in the tropics - 4 0 16; Pande, J. N.; 5 (Delhi ;;New York : Oxford University Press, 1998)
With special reference to India.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Respiratory infections.;Tropical medicine. -- 20; 20; 2